Morfometria em rúmen de cordeiros alimentados exclusivamente a pasto ou com concentrado - Molinari, Mabel (2017)
With the prospect of increased production, the lambs diet evaluation is so important in order to obtain optimal results of weight gain and quality. When we talk about productivity, we must take into consideration diet type offered to animals, thinking about the economic view and also the development of the animal's organism. Feeding causes morphophysiological changes in organs which are part of the nutrients absorption and will generate energy for growing and development. The two treatments used in the present work differ significantly for the volatile fatty acids (VFA) concentration resulting from food fermentation propitiating structural and absorption changes. The treatments used for the extensive system of grass - grazing and the concentrate in confinement. The aim of this paper is a morphometric evaluation of ruminal papillae from different diets, exclusively pasture and concentrate considering best collection site. Data analysis is going to te through rumen blades, with special staining for tissue differentiation and better analysis morphological on the cellular level. The obtained data is going to be analyzed comparing two diets and tissues with each other on the same diet, since there were two collection sites in rumen, dorsal sac and rumen of the meat. This will be done using randomized design and comparison between diets in the rumen tissues and factorial arrangement (2 x 2) for two samples taken from different rumen portions. Measurements will be obtained with the aid of microscope and image analysis of differences generated from the feeding. The histological evaluation sections showed significant differences comparing between treatments and collection site. Animals which concentrate presented more significant measures in relation to the animals which ate pasture propitiating structural changes at the cellular level. Therefore, feeding directly influences the animal growth. In general, it is important to establish specific collection sites to histological evaluations.